2015
DOI: 10.1002/pc.23854
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the compaction behavior of carbon fiber NCF for continuous preforming processes

Abstract: This paper describes the experimental investigation of the compaction behavior of dry single‐ply and multi‐ply fabric stacks (preforms). Utilizing four biaxial (two 0°/90° and two ±45°) and one triaxial (0°±45°) carbon fiber NCF, differing in weight (300 g/m2, 600 g/m2) and type of stitching (tricot, pillar, hybrid), the influence of compaction speed, pre‐compaction cycles, number of layers, and stacking sequence on compaction force was examined. In contrast to other studies, the area of interest is limited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…The results are comparable to the compaction stresses for carbon fibre NCF presented by Grieser et al [12] and are shown on the data in Fig. 10 as well.…”
Section: Preform Compressionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results are comparable to the compaction stresses for carbon fibre NCF presented by Grieser et al [12] and are shown on the data in Fig. 10 as well.…”
Section: Preform Compressionsupporting
confidence: 90%
“…Measured preform compaction data and derived model with comparable compaction stress presented by Grieser et al[12] …”
supporting
confidence: 58%
“…The closest sensor (at 20 mm) starts at slightly lower v F because it had less dwell time under load before wetting by infusion, and thus less time for viscoelastic fiber rearrangement . The closest sensor also had the fastest expansion, thus a slightly stiffer (steeper) curve , compensating for the lower v F and ending up at a similar uncompressed v F to the other sensor locations. The differences in initial v F and stiffness between adjacent sensor locations decreases farther from the inlet.…”
Section: Resultsmentioning
confidence: 98%
“…Many subsequent studies have characterized differences in stiffness, the slope of the compressibility function, analogous to the Young's Modulus in a stress–strain diagram. An extensive review of the literature on compressibility measurement is found in the work by Gutowski and Dillon , which focuses on the dependence of the compressibility on the textile architecture. Composite reinforcements, both dry and lubricated with matrix or other test fluid, exhibit classic time‐dependency characteristics: (1) stress relaxation under load, (2) strain rate dependence, and (3) hysteresis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation